Factors related to healthy sexual and contraceptive behaviors in undergraduate students at university of Seville: a cross- sectional study - Fátima Leon-Larios; Juana Macías-Seda (BMC, 2017)
Abstract Background Young people are a group of population with sexual risk-taking behaviors. Despite efforts to inform them it is common for them to adopt risk conducts during their stay at University. The aim of this research was to assess knowledge, attitudes and experiences on sexual health and contraceptives and factors related to risk behaviors in university students. Methods A cross- sectional analytical study was carried out from February to April 2014 among undergraduate students at University of Seville. A self-administered questionnaire was filled in by participants. Data analysis was performed using SPSS V22. Descriptive statistics were used to show data. A P-value of 5% (two-tailed) was considered statistically significant. Results A total of 566 students responded to the questionnaire. 47.3% (267) were male and 52.6% (297) female. About sexual behavior: 93.3% of participants were sexually active last year. 58.3% had had sex under alcohol effect and 18% under drugs effect. About contraceptive behavior: 86.9% used a contraceptive method during their first sexual relation, the male condom being the most used (90.6%). Currently, the most used contraceptives are the male condom, and hormonal pills. The participants' answers about their knowledge on contraceptives and STIs (sexual transmission infections) showed weaknesses. Participants who had received sexual and contraceptive education showed more knowledge (p < 0.001). We did not find differences about knowledge on contraceptives and STIs by age (p = 0.056). Level of knowledge is less in young people who use coitus interruptus or none as a contraceptive method (p < 0.001). We observed differences by frequency of sex since young people who had sex more frequently showed more knowledge about contraceptives and STI (p < 0.001). There are more women that had a partner than men (p = 0.003) and their attitudes and experiences on sex are healthier. Females showed more knowledge about management of hormonal contraceptives and medical controls (p < 0.001). Conclusion Factors that contribute to having a healthier behavior on sexuality and contraception are age, gender and background in health issues, showing greater knowledge and less risky behavior. Programing reproductive health programs at university should be continued.